A 180 GHz Frequency Multiplier in a 130 nm SiGe BiCMOS Technology - Girg, Thomas; Beck, Christopher; Dietz, Marco; Hagelauer, Amelie Marietta; Kissinger, Dietmar; Weigel, Robert (2016 IEEE 14th International NEWCAS Conference, 2016)
An integrated analog frequency multiplier for a novel high data rate communication system has been developed to multiply a 18 GHz input signal by ten to generate a 180 GHz output signal. With a first step the 18 GHz input signal is fed into a times five edge combiner, which generates an intermediate frequency of 90 GHz. Therefore five different phases with a delta of 72 degree are needed, that are provided by an active allpass filter chain. In a second step the 90 GHz intermediate frequency is given into a double-balanced Gilbert cell mixer. Here, frequency doubling is achieved by feeding the same signal into the LO and RF port of the mixer. Hence, the overall output frequency of 180 GHz results in 180 GHz with a simulated output power of -7 dBm. All simulations are done post-layout. The chip is implemented in a 130 nm BiCMOS technology with a chip area of 0.9 mm x 1 mm.
elib2cris::1512001600,girg2016
Keywords: SiGe BiCMOS; high data rate communication; 180 GHz; simultaneous phase and amplitude regenerative sampling; transmitter; frequency multiplier

An Additive Manufactured K-Band Waveguide Coupler and K-Band Antennas in SLM-Technology - Beck, Christopher; Gabsteiger, Jasmin; Scheitler, Christian Josef; Dietz, Marco; Hagelauer, Amelie Marietta; Weigel, Robert (2020)

Circular Gysel Divider for the Frequency Range from 18 GHz to 26 GHz - Gabsteiger, Jasmin; Beck, Christopher; Dietz, Marco; Weigel, Robert; Lurz, Fabian (2022 52nd European Microwave Conference, EuMC 2022, 2022)
Power dividers are required and used in a wide variety of applications. It is often sufficient to halve the power and divide it evenly between two branches. However, if one branch requires more power than the other, a divider with an unequal power ratio is needed. In the presented work, an equal and an unequal Gysel divider were designed, simulated and measured. Compared to other Gysel splitters, the ones demonstrated here have advantages in size, isolation and losses.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Gysel divider; power divider; unequal

Design of an Integrated Subretinal Implant Using Cellular Neural Networks for Binary Image Generation in a 130 nm BiCMOS Process - Potschka, Julian; Söll, Christopher; Kirchner, Jens; Mardin, Christian Y.; Stadelmayer, Markus; Maiwald, Tim; Breun, Sascha; Kolb, Katharina; Bauch, Andreas; Dietz, Marco; Beck, Christopher; Völkel, Matthias; et al. (IEEE Engineering in Medicine and Biology Conference (EMBC), 2019)

Industrial mmWave Radar Sensor in Embedded Wafer-Level BGA Packaging Technology - Beck, Christopher; Ng, Herman Jalli; Agethen, Roman; Pour Mousavi, Seyed Mehran; Forstner, Hans-Peter; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert; Hagelauer, Amelie Marietta; Kissinger, Dietmar (IEEE Sensors Journal, 2016)
We present highly integrated 60GHz radar transceivers for industrial sensor applications. The bistatic and monostatic transceivers are implemented in the SiGe bipolar technology and packaged using the embedded wafer-level ball grid array (eWLB) technology that allows for direct embedding of the antennas in the package redistribution layer. In this way, very compact and efficient radar frontends comprising all millimeter-wave components can be implemented in an 8 × 8mm2 package. These frontends were soldered on a standard low-cost PCB based on FR4 material. For verification of the proposed frontends, an FMCW radar system was developed and set up within this work. Theoretical considerations and simulations as well as corresponding measurements were carried out for the evaluation of the designed system. The demonstrator results of these embedded radar sensors show excellent system performance at a high integration level.
elib2cris::1512001600,beck2016
Keywords: SiGe RFICs; SiP modules; millimeter-wave circuits; packaging; radar systems

Integrated millimeter-wave transceiver concepts and technologies for wireless multi-Gbps communication - Kissinger, Dietmar; Girg, Thomas; Beck, Christopher; Nasr, Ismail; Forstner, Hans-Peter; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert (IEEE MTT-S International Microwave Symposium, 2015)
elib2cris::1512001600,kissinger2015a

Rotary Coupler in Microstrip Line Design for Data Transmission in the 2.45 GHz ISM Band - Scheiner, Benedict; Beck, Christopher; Lurz, Fabian; Frank, Martin; Michler, Fabian; Weigel, Robert; Kölpin, Alexander (International Microwave and Radar Conference (MIKON), 2020)